Parental partnerships in the governance of schools in the Black townships of Port Elizabeth - Sindiswa Madgie Mbokodi; Prakash Singh (Perspectives in Education, 2011)
This article focuses on the functionality of school-governing bodies (SGBs) as the voice of parents in the governance of schools. After nearly sixteen years since the South African Schools Act 84 of 1996 (SASA) came into effect, the question that still raises many concerns among stakeholders in education is whether Black parents through their SGBs are aptly fulfilling their roles as rightful partners in the governance of their children’s schools. The aim of this study was therefore to determine whether Section 18 of SASA was being appropriately realised in the Black townships of Port Elizabeth. Using the qualitative research method, a sample of ten schools – five primary and five secondary schools – was intentionally selected from the Black townships of Port Elizabeth. A total of forty in-depth open-ended interviews were conducted. The study found that, although the schools had legally constituted SGBs, these SGBs were not functional. The findings of this study shed light on the challenges why a partnership cannot materialise if Black parents do not have the capacity to be partners in the governance of schools. Hence, this study provides new insight into the status quo of Black parental involvement in the governance of schools.